Exploring Nietzsche's Philosophical Idea on Nihilism: “The Question of the Essence of Morality in Humanizing Humans”: Menelisik pemikiran filsafat Nihilisme Nietzsche: “Persoalan Hakikat Moralitas Memanusiakan Manusia” - Faldi Hendrawan; Anak Agung Gede Rai Remawa; I Ketut Sariada (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This article discusses a critical analysis of Friedrich Nietzsche's thought by highlighting the main issues related to the foundations of nihilism and the relevance of two of his central ideas, namely the will to power and the Übermensch, as an effort to overcome the collapse of traditional values. The research uses a qualitative approach with a subjectivism-humanities paradigm through a literature study of Nietzsche's works, especially Thus Spoke Zarathustra and The Will to Power, as well as secondary studies from philosophers and historians of thought. The analytical method is carried out through textual hermeneutics to interpret Nietzsche's aphorisms that are unsystematic but full of philosophical meaning. The results of the study show that Nietzsche's nihilism is not merely a rejection of values, but a diagnosis of the crisis of modern culture that has lost its foundation of meaning; in this context, the will to power functions as a creative human drive to overcome old moral determinations, while the Übermensch becomes an ideal concept of humans who are capable of creating values ​​autonomously. These findings confirm that Nietzsche's thought makes a significant contribution to the development of contemporary philosophy through a rereading of values, freedom, and human existence